Growth evaluation of Oreochromis niloticus fed different concentrations of choline and methionine - Rudy Agung Nugroho; Normala Sari; Retno Aryani; Hetty Manurung; Rudianto Rudianto (Syiah Kuala University, 2020)
A 12-week research was conducted to determine the effects of choline and methionine supplementation on the growth performance of Nile tilapia (Oreochromis niloticus). Three diets, P2-P4 with 0.04; 0.08; 0.12 % of choline; P6-P8 with same levels choline plus methionine (0.15 %); a diet with only 0.15 % methionine (P5); and control without any supplementation (P1) were fed to tilapia (initial weight ±21.05 g) for 12 weeks. Final weight (FW), Body Weight Gain (BWG), Average Daily Gain (ADG), Specific Growth Rate (SGR), and Protein Efficiency Ratio (PER), Feed Efficiency (FE), Feed Intake (FI), Feed Conversion Rate (FCR), Survival Rate (SR), crude protein and lipid of fish fed various levels of choline and methionine were also measured. The results showed that tilapia fed 0.04 % choline (P2) had significantly better growth parameters and feed efficiency than other groups. Meanwhile, SR of tilapia was not affected by any supplementation of choline and methionine. The tilapia fed 0.08% choline (P3) showed the highest crude protein (52.50 ± 0.98 %) in the carcass proximate but low lipid (19.03 ± 0.10 %). This finding demonstrated the benefits of choline (0.04-0.08 %) supplementation in the tilapia diet in term of growth and carcass proximate.